Autochtonizm i autochtonizacja - Kwaśniewski, Krzysztof (Wydział Prawa i Administracji UAM, 1987)
The article discusses the above concepts as phenomena and ideologies concerning a generic bond between a given community and the region or national territory of their residence; furthermore, it discusses the tendencies to retain or to form such a bond. In the age of modern migrations, autochthonism can neither be isolationism nor pure nativism. It must be connected with the ideology of revitalisation, which allows for the autochthonisation of immigrants without denying the autochthonism of residents and without destroying the cultural identity of the region or the nation. The autochthonisation of immigrants in the regions which are their ideological homeland but at the same time lack native population (like in some parts of Polish Regained Territories) cannot be a mere ideology but should be supported by adequate organizational, cultural and political measures. Such efforts must be undertaken, for neither isolationism nor programmatic allochtonism can satisfy the natural need of "being from somewhere".
Autochthonism and Autochthonisation